PEMBERHENTIAN DENGAN HORMAT TIDAK ATAS PERMINTAAN SENDIRI SEBAGAI PEGAWAI NEGERI SIPIL OLEH KEMENTERIAN HUKUM DAN HAM REPUBLIK INDONESIA TERHADAP PELANGGARAN DISIPLIN BERAT - HENDRI BUDI ISKANTO,SE A. 2021131003, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses the dismissal with respect not his own request as civil servants by the Ministry of Justice and Human Rights of the Republic of Indonesia to severe disciplinary violations. The method used in this study is a normative approach - sociological. From the results of this thesis research was concluded Dismissal with respect not his own request as a civil servant against Syamsul Bahri CS Civil Servants in the Ministry of Justice and Human Rights of the Republic of Indonesia is in conformity with Article 20 paragraph (1) letter a Government Regulation No. 53 Year 2010 on discipline of Civil Servants. This compliance is viewed from various aspects, namely: (1) Law Enforcement, In accordance with Article 20 paragraph (1) letter a that the authorities to establish the imposition of disciplinary punishment for a Civil Servant regulator youth level I, class room II / b Officers Trustees Personnel in this case is the Minister of Justice and Human Rights of the Republic of Indonesia. (2) Violation type, which type violations committed by Syamsul bahri CS is a kind of violation of article 7 paragraph that severe disciplinary violations in the form of dismissal with respect not his own request as a civil servant. Factors that lead to violations of discipline the Civil Service of the Ministry of Justice and Human Rights of the Republic of Indonesia is the internal factors that consist of quality human resources personnel are relatively inadequate, as well as the level of welfare as their salary felt still lacking and insufficient to meet Civil Servants family needs. External factors that include cultural and environmental factors, affecting the work discipline of Civil Servants. Recommendations In the freedom of action of the competent authorities in this case the Minister of Justice and Human Rights, needs to be maintained firm in penalizing the Civil Servants within the Ministry of Justice and Human Rights who commit severe violations of discipline. In addition, with the case experienced by Syamsul CS is expected to be a deterrent and warning other Civil Servants working in the Ministry of Justice and Human Rights, to further improve its performance so that such incidents can be minimized. Should guidance regarding discipline Civil Servants always done routinely considering the attitudes and behavior of Civil Servants are always influenced by the local work culture. In order for the implementation of the tasks for the Civil Service is more effective and efficient it is expected that the Ministry of Justice and Human Rights to immediately make a rule that contains the code of conduct within the Ministry of Justice and Human Rights of the Republic of Indonesia.Keywords: Dismissal With Regards Not On Demand Alone For Civil Servants ABSTRAKTesis ini membahas pemberhentian dengan hormat tidak atas permintaan sendiri sebagai pegawai negeri sipil oleh Kementerian Hukum Dan Ham Republik Indonesia terhadap pelanggaran disiplin berat. Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan Normatif - sosiologis. Dari hasil penelitian tesis ini diperoleh kesimpulan Pemberhentian dengan hormat tidak atas permintaan sendiri sebagai Pegawai Negeri Sipil terhadap Syamsul Bahri CS Pegawai Negeri Sipil di Kementerian Hukum Dan Ham Republik Indonesia sudah sesuai dengan pasal 20 ayat (1) huruf a Peraturan Pemerintah Nomor 53 Tahun 2010 tentang Disiplin Pegawai Negeri Sipil. Kesesuaian ini dilihat dari berbagai macam aspek, yaitu: (1) Penegak Hukum, Sesuai dengan Pasal 20 ayat (1) huruf a bahwa pihak yang berwenang untuk menetapkan penjatuhan hukuman disiplin bagi seorang Pegawai Negeri Sipil pengatur muda tingkat I, golongan ruang II/b adalah Pejabat Pembina Kepegawaian dalam hal ini adalah Menteri Hukum dan Ham Republik Indonesia. (2) Jenis Pelanggaran, yang mana Jenis Pelanggaran yang dilakukan oleh Syamsul bahri CS adalah jenis pelanggaran yang ada dalam pasal 7 ayat yaitu pelanggaran disiplin berat berupa pemberhentian dengan hormat tidak atas permintaan sendiri sebagai Pegawai Negeri Sipil. Faktor-faktor yang menyebabkan terjadinya pelanggaran disiplin Pegawai Negeri Sipil pada Kementerian Hukum Dan Ham Republik Indonesia adalah faktor internal yang terdiri dari kualitas sumberdaya manusia aparatur yang relatif kurang memadai, demikian juga dengan tingkat kesejahteraan seperti gaji yang diterima dirasakan masih kurang dan tidak cukup untuk memenuhi kebutuhan keluarga Pegawai Negeri Sipil. Faktor External yang meliputi faktor budaya dan lingkungan, mempengaruhi disiplin kerja Pegawai Negeri Sipil. Rekomendasi Dalam kebebasan bertindak pejabat yang berwenang dalam hal ini Menteri Hukum dan Ham , perlu dipertahankan ketegasannya dalam menjatuhkan sanksi kepada para Pegawai Negeri Sipil di Lingkungan Kementerian Hukum dan Ham yang melakukan pelanggaran disiplin berat. Selain itu, dengan adanya kasus yang dialami oleh Syamsul CS ini, diharapkan dapat menjadi efek jera dan peringatan Pegawai Negeri Sipil lain yang bekerja di lingkungan Kementerian Hukum dan Ham , untuk lebih meningkatkan kinerjanya sehingga kejadian semacam ini dapat diminimalisir. Seyogyanya pembinaan mengenai disiplin Pegawai Negeri Sipil selalu dilakukan secara rutin mengingat sikap dan perilaku Pegawai Negeri Sipil selalu dipengaruhi oleh budaya kerja setempat. Agar pelaksanaan tugas bagi Pegawai Negeri Sipil lebih efektif dan efisien diharapkan kepada Kementerian Hukum dan Ham untuk segera membuat peraturan yang memuat kode etik dilingkungan Kementerian Hukum dan Ham Republik Indonesia.Kata Kunci: Pemberhentian Dengan Hormat Tidak Atas Permintaan Sendiri Sebagai Pegawai Negeri Sipil